2022
DOI: 10.1126/sciadv.abl8423
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-mediated triboelectric nanogenerator for powering on-demand transient electronics

Abstract: The ultrasound-mediated transient materials enable the management of biodegradation processes for implantable electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(138 citation statements)
references
References 34 publications
0
121
0
Order By: Relevance
“…Therefore, as an alternative, a fully biodegradable ultrasound energy harvester could be developed by adopting the present prototype but using transient, biodegradable high-performance piezo-/triboelectric polymers, biodegradable metals, and novel structural strategies for realizing highperformance transient, biodegradable ultrasound energy harvesters. [20,87]…”
Section: Envisioned Energy Systems For Future Directions and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as an alternative, a fully biodegradable ultrasound energy harvester could be developed by adopting the present prototype but using transient, biodegradable high-performance piezo-/triboelectric polymers, biodegradable metals, and novel structural strategies for realizing highperformance transient, biodegradable ultrasound energy harvesters. [20,87]…”
Section: Envisioned Energy Systems For Future Directions and Challengesmentioning
confidence: 99%
“…The ex vivo evaluation of the device in a porcine tissue revealed that the device stopped generating electric power when exposed to an ultrasound intensity of 3.0 W cm −2 for 20 min and thus, demonstrated a promising hybrid technology for powering transient, biodegradable electronic devices/systems. [ 87 ]…”
Section: Energy Transfer Systemsmentioning
confidence: 99%
“…[58,59] With the rapid development of the world, various electronic devices tend to be miniaturized, diversified, personalized and routinely developed, [60][61][62][63][64][65][66][67][68][69][70][71][72] and the resulting energy needs require us to develop new forms of universal energy harvesting. [34,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] Recently, researchers around the world have proposed a series of biomechanical energy harvesting mechanisms, such as triboelectric nanogenerators (TENGs), [91][92][93][94][95][96][97][98][99][100][101][102][103][104]…”
Section: Advances In Bioinspired Triboelectric Nanogeneratorsmentioning
confidence: 99%
“…A triboelectric nanogenerator (TENG), based on the Maxwell’s displacement current [ 26 , 27 ], can effectively convert random mechanical energy such as human movement [ 28 , 29 ] and environmental energy [ 30 , 31 ] into electric energy. The TENG possesses excellent electric performance and mechanical properties, including various working modes [ 32 , 33 , 34 , 35 ], high output voltage [ 36 , 37 ], high energy conversion efficiency [ 38 , 39 ], and flexibility and biocompatibility [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%